(untitled) (Indian Journal of Chemistry (IJC), 2026)
A molecular hybridization strategy was employed to synthesize 7[(1-benzyl-1H-1,2,3-triazol-4-yl)methyl]-3-methyl-4-aryl-7H-isoxazolo[5,4-b]pyrazolo[4,3-e]pyridine-5-amines (6) by incorporating pyrazolo-pyridine on isoxazole nucleus with 1,2,3-triazole fragment on pyrazole nitrogen as potential antimicrobial agents. The structures of the newly synthesized compounds were confirmed by IR, NMR, and Mass spectrometry. The compounds (6a-h) screened for their in vitro antimicrobial activity showed promising activity compared to standard drugs. Especially compounds 6g and 6h exhibited high antibacterial and antifungal activity with respect to standard drugs Ciprofloxacin and Fluconazole respectively. Furthermore, molecular docking analysis also supported the data of antimicrobial activity by revealing high binding affinity scores across the entire series.